Numerical study of a novel single-stage Vuilleumier type pulse tube cryocooler. (April 2019) - Wang, Jue; Pan, Changzhao; Chen, Liubiao; Xi, Xiaotong; Wu, Xianlin; Wang, Junjie; Zhou, Yuan
Abstract: The Vuilleumier cryocooler (VMC) is a novel kind of Stirling cryocooler driven by thermal compressor. To realize no moving parts at the cold end of VMC, this paper presents a study of the single stage Vuilleumier-type pulse tube (VM-PTC) cryocooler driven by thermal compressor. First, the structure and numerical model of VM-PTC are introduced. Then, the operating mechanism and performance of cold phase shifter including capillary tubes and double-inlets are studied. At last, a preliminary experiment is carried out to know about the practical performance of the single-stage VM-PTC. It can obtained no-load temperature of 12.1 K and 0.7 W cooling power at 20 K by using 46 W precooling power at 77 K.